Management of Violence in the Emergency Department A government hospital in the eastern region - Kittidilok, Jariya; Puttpitukpol, Somjai; Luengsomnapa, Yotsaphon (Journal of Public Health Nursing, 2025)
The purpose of this descriptive research is to explore the guidelines for managing violence in emergency departments, A government hospital in the eastern region. The research consists of 3 phases. Phase 1: in-depth interview of ten personnel who in charge of providing services in the emergency department. Phase 2:evaluate the perception nurses about the management procedure of violence in the emergency department of A government hospital in the eastern region. Phase 3: in-depth interview of the head nurse of A government hospital in the eastern region for the policy to manage the violence in emergency department. The questionnaire, developed by the researcher, consisted of 3 parts, 1) general information 2) the management of violence in the emergency department and 3) violence management guidelines. The content validity of the instruments were analyzed by 6 experts. Data were analyzed by descriptive statistics and content analysis. The results found that in the past year 100% of the professional nurses of the emergency department, A government hospital in the eastern region have been verbally abused. The incidence was found to be 1-2 times/year at 75%, 3-5 times/year at 16.6%, and more than 6 times/year at 8.4%. The factors that led to the violence were dissatisfaction from having to wait for service for a long time at 30%, followed by the patients being drunk at 27.14%, the patients having mental illness at 21.43%, and insufficient communication between nurses and relatives at 17.14%, respectively. Managing when violence occurs are modified of severity classification criteria and conducting nursing practice guidelines to be different according to severity levels. Establish precise guidelines to care for the personnel who have been subjected to violence. In terms of violence prevention, nursing practices are set by providing information to relatives every 30 minutes. In cases where service recipients are found to be intoxicated or mentally ill, security personnel are assigned to be at the bedside during procedures. Training is also provided to all levels of staff on negotiation, self-defense, violence control, and virtual reality rehearsals.